If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4(s + 3t) = 0 6 + (s * 4 + 3t * 4) = 0 6 + (4s + 12t) = 0 Solving 6 + 4s + 12t = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 4s + -6 + 12t = 0 + -6 Reorder the terms: 6 + -6 + 4s + 12t = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 4s + 12t = 0 + -6 4s + 12t = 0 + -6 Combine like terms: 0 + -6 = -6 4s + 12t = -6 Add '-12t' to each side of the equation. 4s + 12t + -12t = -6 + -12t Combine like terms: 12t + -12t = 0 4s + 0 = -6 + -12t 4s = -6 + -12t Divide each side by '4'. s = -1.5 + -3t Simplifying s = -1.5 + -3t
| 99-n=66 | | 28+z=123 | | 1076=x^2 | | 59+y=104 | | y=-10+-8x+2x^2 | | a-47=29 | | 6x+13-3x-7= | | 228=12x | | y=2x^2-8x-10 | | y-16+15=60 | | 36-2=-45 | | 2.8+2.2+x=0 | | 4.7+10m=6.98 | | 10x+15+13x+26x=180 | | 13x+7=39 | | 72/y-6=6 | | C=5x^2-200x+4000 | | 2+5+x=0 | | 3x^2+x=3.75 | | X^2-46x+225=0 | | 400=x^2 | | (x+15)(x+5)(10x-20)=180 | | t/5-4=13 | | 5.9x=-17.11 | | -2*(t-1)=3*(6t-6) | | (x^2+5x-7)(x^2-x+4)-(x+2)(x-3)= | | 10x^2-23=-12 | | y+7x=114 | | 4x-.2=1 | | F(x)=-2x^2-8x+2 | | -7n^2-7n-6=0 | | (3x^2+4)(2x^2-3)+4x(3x-5)= |